Geriatric depression and alexithymia in family caregivers of patient with dementia: A cross sectional study - Tartaglini, Maria Florencia (2019)
Caring for patients with dementia is a stressful process for caregivers which increases the risk of physical and mental problems, among which depressive disorders stand out. Aim: To determine the prevalence and predictors of Geriatric Depression and Alexithymia in elderly people.